Experimental Study of Level and Flow Control - Abdul Aziz, Ayu Najieha; Rahmad, Rohani (Progress in Engineering Application and Technology, 2021)
In chemical engineering system, the level and flow control in tanks was very significant but the problem occurred was the control of liquid level in tanks and flow between tanks. Thus, an experimental study of level and flow control was conducted using Level Flow Process Control Training System (Model: SE 665). The main objective of this study was to discuss and compare the results of changing in derivative time ( towards the level and flow control where the results was obtained through the application of SOLDAS® IR4.0. In this study, the level and flow control were controlled using Proportional Integral and Derivative (PID) controller. The study was conducted at the Instrumentation and Process Control Laboratory located at Universiti Tun Hussein Onn Malaysia (UTHM), Pagoh. At the end of this study, the change in derivative time ( towards the PID Level and Flow control were expected to influence the results obtained based on the process variable (PV), setpoint (SP) and manipulated variable (MV).